Paid parental leave and child development: Evidence from the 2007 German parental benefit reform and administrative data - Mathias Huebener; Daniel Kuehnle; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper examines the effects of a substantial change in publicly funded paid parental leave in Germany on child development and socio-economic development gaps. For children born before January 1, 2007, parental leave benefits were means-tested and paid for up to 24 months after childbirth. For children born thereafter, parental leave benefits were earnings-related and only paid for up to 14 months. Higher-income households benefited more from the reform than low-income households. We study the reform effects on children's language skills, motor skills, socio-emotional stability, and school readiness using administrative data from mandatory school entrance examinations at age six and a difference-in-differences design. We find no impact of the reform on child development and socio-economic development gaps. The effects are precisely estimated and robust to various model specifications and sample definitions. Our resultssuggest that such substantial changes in parental leave benefits are unlikely to impact children's development. These findings are consistent with recent studies showing that temporary unrestricted transfers and maternal part-time employment have a limited impact on parental investments in their children.
Keywords: J13; J18; J22; J24; 330; parental leave benefit; child development; skill formation; parental investments; school readiness; motor skills; language skills; socio-emotional stability; socio-economic differences